Manufatura aditiva de mecanismos sem montagem aplicada no desenvolvimento de um efetuador flexível - Nakasone, Fábio Kiei (Universidade Federal de São Carlos, 2024)
The additive manufacturing (AM) process, or 3D printing, can be applied both to the production of prototypes for visual purposes only, as well as functional parts for final applications. AM enables the production of complex and personalized parts, without the need for several manufacturing process steps carried out on conventional equipment. Additive manufacturing is applied in different areas, including industrial automation using flexible devices produced through this process, aiming for greater efficiency in production lines with the proportional distribution of low impact forces, greater degree of freedom of effectors and the interface between machines and humans in object manipulation systems. The objective of this work is to develop a study on additive manufacturing of non- assembly mechanisms, applied to the design of flexible effectors for educational applications, and to analyze the mechanical behavior of the physical structure, through tests on a test bench in handling objects of different shapes. Additive manufacturing processes, printing of mechanisms without assembly, materials used to manufacture the effectors, sensors used, textured surfaces, types and drive systems of flexible devices are presented. The sequence of activities consists of developing the effector, selecting the drive mechanism, producing the effectors by AM, developing the drive mechanism, selecting textures, carrying out tests and analyzing the data obtained. During testing of handling objects with different geometries and masses, tables and graphs were generated demonstrating the best performance of the prototype in a vertical position and with a homogeneous EVA texture.
Additive manufacturing of non assembly mechanisms applied to the development of a flexible effector
Keywords: Impressão 3D; Efetuador; Garra; Robótica; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO